Peningkatan Nilai Gizi, Sifat Organoleptik dan Sifat Pati Sagu Mutiara dengan Penambahan Buah Kenari (Canarium ovatum) - Vita N. Lawalata; I Wayan Budiastra; Bambang Haryanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Sago is a potential local crop for food diversification program. The research aims to 1) improve the nutrition of pearl sago product through canary addition 2) evaluate of chemical-physical and organoleptic quality of pearl sago 3) study the influence of packaging to the product during storage and 4) to predict the shelf life of pearl sago product. The research was done in two steps : I) product development through canary addition of 0 %, 3 %, 6 %, 9 %, 12 % and 15% to pearl sago. 2) packaging and storage the pearl sago using LDPE and PP/alufo/PP. The result shows that canary addition of 9 % and PP/alufo/PP packaging is the best treatment for pearl sago. The product has contents of moisture, protein, fat, ash, carbohydrate and energy of 5.83%, 5.53%, 6.72%, 0.81%, 81.14%, 407.17 Kal, respectively, with shelf life of 256 days.